The development of Islamic finance literature in response to economic turbulence: A systematic review of financial stability strategies - Pusparini, Martini Dwi; Fianto, Bayu Arie; Sukmaningrum, Puji Sucia; Mohd Dali, Nuradli Ridzwan Shah Bin (Journal of Islamic Economics Lariba, 2025)
IntroductionEconomic turbulence remains a persistent challenge globally, as evidenced by historical crises such as the Great Depression, the 2007–2009 Global Financial Crisis, Brexit, and the COVID-19 pandemic. These events have underscored the necessity for resilient and ethically sound financial frameworks. Islamic finance has gained attention as a viable alternative financial system, potentially offering enhanced stability during periods of economic instability.ObjectivesThis study systematically reviews existing literature on the development and responses of Islamic finance during various economic disturbances. It aims to identify how Islamic financial institutions adapt their strategies, products, and services in response to crises, and highlight areas for future research.MethodThe systematic literature review method was used, analyzing 76 academic articles published between 2007 and 2023 from high-quality journals (Q1 and Q2) indexed in the Scopus database. Articles were carefully screened using defined inclusion and exclusion criteria to ensure relevance to economic crises and Islamic finance.ResultsFindings reveal that Islamic financial markets and Islamic banking were the predominant topics, demonstrating varied responses to economic shocks. Islamic banks, employing profit-loss sharing models, exhibited resilience during economic downturns, though inefficiencies in profitability and capitalization were noted. Islamic financial markets, characterized by ethical investments and low leverage, provided diversification advantages but remained vulnerable due to limited portfolio diversity. Additionally, Islamic social finance tools such as zakat and waqf were beneficial in supporting economic recovery, especially during the COVID-19 crisis.ImplicationsThe study suggests that governments and policymakers should promote profit-loss sharing models in Islamic banking and encourage greater diversification in Islamic financial markets to enhance resilience. Additionally, Islamic social finance should be further integrated into economic recovery strategies to mitigate crisis impacts.Originality/NoveltyThis research uniquely synthesizes insights into the adaptive responses of Islamic financial institutions across historical economic crises, addressing a significant knowledge gap in Islamic finance literature. By providing comprehensive future research directions, it contributes valuable guidance for scholars, practitioners, and policymakers aiming to develop sustainable and resilient financial systems.